AN EVALUATION OF THE IMPLEMENTATION OF CURRICULUM 2013 AT PRIMARY SCHOOLS IN BOGOR - Wulandari, Arum; Sarkadi, Sarkadi; Puspitasari, Kristanti Ambar (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
This research aims to evaluate the implementation of Curriculum 2013 at primary schools in Bogor. The evaluation includes school objectives, learning tools, lesson planning, learning implementation, assessment, and learning outcomes. This research uses the CIPP (Context, Input, Process, Product) evaluation from Stufflebeam. The subjects of this study were teachers from five schools, school documents, and the school facilities. Data collection techniques used are documentation, observations, questionnaires, and interviews. Data analysis techniques used the Miles and Huberman interactive model analysis method. The results of the research show that: (1) there are school objectives that are still not in line with the objectives of the Curriculum 2013; (2) learning tools have not been fully met; (3) the lesson planning, implementation and assessment of learning are still not in accordance with the Curriculum 2013; and (4) the learning outcomes of students have reached the minimum criteria of completeness (KKM). Based on the results of this research, recommendations were obtained that could be used as reference for curriculum implementation.